Sodium-Mediated Reductive anti-Dimagnesiation of Diarylacetylenes with Magnesium Bromide - Yamaguchi, Haruka; Takahashi, Fumiya; Kurogi, Takashi; Yorimitsu, Hideki (Synthesis, 2024)
Diarylacetylenes undergo anti-dimagnesiation using magnesium bromide and sodium dispersion to afford (E)-1,2-dimagnesioalkenes. This dimagnesiation utilizes simple magnesium bromide as a reduction-resistant electrophile, contrasting with the previously reported dimagnesiation using tricky organomagnesium halides. The resulting vicinal double Grignard reagents react with various electrophiles to yield multisubstituted alkenes stereoselectively.
Keywords: organomagnesium compounds; sodium dispersion; alkynes; electron transfer; multisubstituted alkenes